ETHNOBOTANICAL RECORDS OF NOT YET DOCUMENTED THERAPEUTIC EFFECTS OF SOME POPULAR BULGARIAN MEDICINAL PLANTS - Kozuharova, Ekaterina; Benbassat, Niko; Getov, Ilko (Emirates Journal of Food and Agriculture, 2014)
Despite the existence of many relevant publications, and of reliable records of the traditional empiric data about medicinal plants in Bulgaria, over the last few years we found quite a lot of hitherto undocumented data about the healing properties of plants. In order to test the contemporary status of the traditional knowledge about medicinal plants, we performed the study as a Rapid Ethnobotanical Appraisal in the way of structured interview based on fixed questions namely what plants are used against certain health disorders. We therefore interviewed 183 people during the summer of 2011: some whom we knew to be particularly interested in medicinal plants and traditional ways of healing, and also a random sample of people of different ages. These subjects were all over l8. The survey was called ?Granny had a cure for this.? (or ?Granny knew how to cure this.?) In this paper we present data for remedial properties of popular medicinal plants which have not been documented in the literature yet - Pulsatilla pratensis - fresh leaves used as compress against exostoses, Sambucus ebulus - immature fresh leaves used for compress in case of exostoses, Primula veris - leaves infusion used against vertigo and Nepeta nuda - application of decoction internally against cystitis and prostate gland inflammation as well as externally against wounds and on the stock udder against mastitis. Comparative analysis of relevant studies was also done.